Exploring the perceptions of obesity, health habits, stigma, and eating behaviors in Brazil - Luiz F. Viola; Fabiana Mandel; Cynthia M. Valerio; Maria Augusta Bernardini; Bruno Halpern (Diabetology & Metabolic Syndrome)
Abstract Background Obesity is a chronic and complex disease influenced by various factors that hinder weight loss and maintenance. However, perceptions of obesity are often marked by stigma. This study assessed perceptions of obesity, weight stigma, health habits, and emotional eating in a representative sample of the Brazilian population. Methods This cross-sectional study included a representative sample of 2560 Brazilian participants. Data were collected from structured online questionnaires covering demographic aspects, perceptions of obesity, stigma, health habits, and behaviors related to emotional eating. Results The prevalence of obesity in the sample was 26%. However, 61% of these individuals did not receive a formal diagnosis. Although 76% of the participants considered obesity a disease, 65% believed that diet and exercise were sufficient treatments. Only 5% of the participants with obesity considered 10% weight loss beneficial for associated comorbidities. It was widely believed that normalizing body mass index (BMI) is necessary for positive health outcomes. Emotional eating behaviors were slightly more prevalent among individuals with obesity (25%) but were present across all BMI ranges. Conclusions The findings of this investigation underscore the necessity for comprehensive education regarding obesity as a complex multifactorial condition. They emphasize the importance of promoting awareness of the benefits associated with modest weight reduction, improving the diagnosis and documentation of obesity in clinical settings, and implementing targeted interventions to address misconceptions concerning treatment modalities and the impact of emotional eating behaviors.